Устройство аварийной защиты ядерного реактора - Артельный А. Г. Александр Григорьевич; Артельный Ю. А. Юрий Александрович; Гаврилов П. М. Петр Михайлович; Иванов В. А. Вячеслав Александрович; Кохомский А. Г. Александр Георгиевич; Цыганов А. Г. Александр Александрович; Чуканов В. Б. Виктор Борисович
опубл. 27.07.08